2007
DOI: 10.1007/s00436-007-0771-9
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and molecular identification of Anisakis spp. from the North African coasts of Mediterranean Sea

Abstract: Larval forms of the genus Anisakis were reported infecting several fish species from the North African coasts of central Mediterranean Sea. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis was used to investigate the occurrence of larval forms of different Anisakis species in teleost fishes and squid from North African coasts of the Mediterranean Sea and to establish the geographical and host range of these parasites in this area. A total of 282 Anisakis larvae were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 31 publications
3
56
1
1
Order By: Relevance
“…between regions. From the three species identified by molecular markers in the present work, Anisakis pegreffii is common throughout the Mediterranean, having been found at Madeira (Pontes et al 2005), Morocco and Mauritania (Mattiucci et al 1997;Farjallah et al 2008), extending its distribution to the southern Atlantic (Mattiucci and Nascetti 2008). This anisakid together with A. typica, also found in the present work, are parasites of dolphins, confined to surface waters and from 35°N to the austral region (see Mattiucci et al 1997).…”
supporting
confidence: 78%
“…between regions. From the three species identified by molecular markers in the present work, Anisakis pegreffii is common throughout the Mediterranean, having been found at Madeira (Pontes et al 2005), Morocco and Mauritania (Mattiucci et al 1997;Farjallah et al 2008), extending its distribution to the southern Atlantic (Mattiucci and Nascetti 2008). This anisakid together with A. typica, also found in the present work, are parasites of dolphins, confined to surface waters and from 35°N to the austral region (see Mattiucci et al 1997).…”
supporting
confidence: 78%
“…The heterogeneity was observed at those sites diagnostic for each species. The heterogeneity was only observed in areas where sympatric coexistence occurred (Abollo et al 2003, Farjallah et al 2007). ITS sequences from anisakids isolated from Baltic Sea herring had a T at position 173, whereas other A. simplex s.s. possessed a C. These herring anisakids could represent the second 'variant' in a hybrid situation; however, they did not display the corresponding polymorphic nucleotides at the other positions observed in anisakids from RVS salmon.…”
Section: Asp Ay821749 Tc--cgta Ta-cagttt--gtgtgatc-tatgt--caa Cgcaamentioning
confidence: 99%
“…The larvae have been found in scombrids and carangids such as Auxis thazard thazard and Thunnus thynnus from Brazil (SW Atlantic); Scomber japonicus and Trachurus picturatus from the NE Atlantic off Madeira; Euthynnus affinis, Scomberomorus commerson, Sarda orientalis and C. hippurus from the west Indian Ocean off Somalia; and from Merluccius merluccius from the eastern Mediterranean Sea . Further records were provided by Mattiucci et al (2005) from Florida, Farjallah et al (2008) from the Mediterranean coast of North Africa (Scomber scombrus, M. merluccius, Phycis phycis), from Australia by Cannon (1977) and more recently by Shamsi (2007Shamsi ( , 2014 and Jabbar et al (2012) from the Great Barrier Reef, and by Chen & Shih (2015) from Taiwan. Kuhn et al (2013) have already summarized the worldwide known hosts for genetically confirmed worms, naming 26 different teleost species.…”
Section: Hosts and Life Cyclementioning
confidence: 99%
“…typica, the most common species in tropical fishes, has been identified from the southwest Atlantic (Brazil; Nadler et al 2005), west (Florida; Mattiucci et al 2005) and east Atlantic (Madeira, Portugal; Pontes et al 2005), the Mediterranean (North Africa; Farjallah et al 2008), the central Pacific (Hawaii and Moorea; Kuhn et al 2013, Palm & Bray 2014, and most recently from free-living Indo-Pacific bottlenose dolphins Tursiops aduncus off the Hurghada coastline in the northern Red Sea, Egypt (Kleinertz et al 2014b). Shamsi (2014) summarized the knowledge about Australian Anisakis spp., and identified the species A. brevispiculata, A.…”
Section: Introductionmentioning
confidence: 99%